The Radiation Assessment Detector (RAD) Investigation - Hassler, D. M.; Zeitlin, C.; Wimmer-Schweingruber, R. F.; Böttcher, S.; Martin, C.; Andrews, J.; Böhm, E.; Brinza, D. E.; Bullock, M. A.; Burmeister, S.; Ehresmann, B.; Epperly, M.; et al. (Space science reviews, 2012)
The Radiation Assessment Detector (RAD) on the Mars Science Laboratory (MSL) is an energetic particle detector designed to measure a broad spectrum of energetic particle radiation. It will make the first-ever direct radiation measurements on the surface of Mars, detecting galactic cosmic rays, solar energetic particles, secondary neutrons, and other secondary particles created both in the atmosphere and in the Martian regolith. The radiation environment on Mars, both past and present, may have implications for habitability and the ability to sustain life. Radiation exposure is also a major concern for future human missions. The RAD instrument combines charged- and neutral-particle detection capability over a wide dynamic range in a compact, low-mass, low-power instrument. These capabilities are required in order to measure all the important components of the radiation environment. RAD consists of the RAD Sensor Head (RSH) and the RAD Electronics Box (REB) integrated together in a small, compact volume. The RSH contains a solid-state detector telescope with three silicon PIN diodes for charged particle detection, a thallium doped Cesium Iodide scintillator, plastic scintillators for neutron detection and anti-coincidence shielding, and the front-end electronics. The REB contains three circuit boards, one with a novel mixed-signal ASIC for processing analog signals and an associated control FPGA, another with a second FPGA to communicate with the rover and perform onboard analysis of science data, and a third board with power supplies and power cycling or “sleep”-control electronics. The latter enables autonomous operation, independent of commands from the rover. RAD is a highly capable and highly configurable instrument that paves the way for future compact energetic particle detectors in space.